2020
DOI: 10.1186/s12916-020-01801-9
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in adult HIV-infected patients on antiretroviral therapy: a systematic review and meta-analysis

Abstract: Background Antiretroviral therapy (ART) alters platelet reactivity, and as a consequence, patients living with HIV may be at an increased risk of cardiovascular disease (CVD). The current evidence on platelet activation levels in patients with HIV remains inconclusive. We therefore aimed to systematically synthesise evidence on the association of platelet activation in HIV-infected patients on successful treatment. Methods Electronic databases were searched from inception until November 2019. Studies were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
(173 reference statements)
0
20
0
Order By: Relevance
“…Several investigations have found that patients living with HIV have higher levels of P-selectin than people who are not infected. This backs up the observation that adult HIV-infected patients have higher levels of platelet activation [ 37 ]. Importantly, these levels were found to persist in follow-up investigations after 3 to 24 months of effective ART [ 38 ].…”
Section: P-selectin In Human Diseasesmentioning
confidence: 87%
“…Several investigations have found that patients living with HIV have higher levels of P-selectin than people who are not infected. This backs up the observation that adult HIV-infected patients have higher levels of platelet activation [ 37 ]. Importantly, these levels were found to persist in follow-up investigations after 3 to 24 months of effective ART [ 38 ].…”
Section: P-selectin In Human Diseasesmentioning
confidence: 87%
“…Next, we analyzed the phenotype of platelet-CD4 + T cell aggregates in patients infected with HIV-1. Previous reports have demonstrated that HIV-1-infected patients display elevated platelet activation with or without ART (28,56). The activation state of platelets in platelet-CD4 + T cell aggregates was analyzed by detecting CD62P expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is increased platelet activity leading to increased immune activation in PLHIV, which is associated with the increased CVD risk. This increased platelet activity is not completely abolished by ARV drugs, 30 36 and indeed, there are reports that ARV drugs may enhance platelet activation. 30 37–39 Therefore, low-dose ASA added onto ARV drugs may be the more appropriate intervention than high-dose ASA for reducing CVD risk in PLHIV.…”
Section: Introductionmentioning
confidence: 88%
“…[37][38][39] Protease inhibitor (PI)-based ART has also been implicated in increasing platelet activation with patients on PI-based ART having up to double levels of platelet activation compared with ARV naïve counterparts. 30 In view of this possible drawback of ARV drugs on immune and platelet activation, an additional drug may be necessary for effective prevention of non-infectious comorbidities including CVD in HIV infection. 29 Aspirin or acetylsalicylic acid (ASA) is a drug with antiplatelet and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation